Factors Affecting Effectiveness of the Operation in the Internal Quality Assurance for Rajamanagala University of Technology Thanyaburi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purposes of this survey research were 1) to study the level of factors affecting the effectiveness of the operation in the internal quality assurance for Rajamangala University of Technology Thanyaburi (RMUTT), and 2) to propose the development guidelines for the effective operation of the internal quality assurance for RMUTT. The samples were 400 RMUTT personnel. The instruments used in this research were a questionnaire. The data were analyzed by percentage, mean, standard deviation, Pearson's correlation coefficient, and multiple regression. The research results found that factors affecting the effectiveness of the operation in the internal quality assurance for RMUTT was at a high level, and were ordered as follows: organizational leaders, organizational culture, management, personnel, resources, and ICT. The results of the overall effectiveness of the operation in the internal quality assurance for RMUTT was also at a high level, and could be ordered as follows: Action, Plan, Check and Do (the PDCA cycle). The hypothesis testing with multiple regression revealed that the regression coefficient of the overall effectiveness of the operation in the internal quality assurance for RMUTT was 0.892. For the development guidelines for the effective operation of the internal quality assurance for RMUTT, it is suggested that there should be getting related personnel on the same page, everyone takes full responsibility to fulfil criteria and indicators, and understands the assessment process. Moreover, the university personnel should be continuously trained on internal quality assurance.